O Prêmio INOVES : a sociologia de um sucesso - Freitas, Mariana da Rós (2012)
The litany reports known much more about bad governments, especially in developing countries than on their innovative practices. In the Brazilian agencies in recent years there has been a constant presence and reiterated the idea of an administrative reform. The simplest observation has shown low levels of efficiency, effectiveness and transparency in public institutions. The present study aims to bring out, contrary to common sense, an example of good government - the Prêmio INOVES. Thus arise the concepts of efficiency and effectiveness in the public sector. As well, the exposure of the state of a scenario that shows the Espírito Santo opened the prospects for change. In this sense, through the sociology of organizations, we seek to experience aspects of the reality of the Prêmio INOVES presented to explain particular concepts from the theory of human relations and tour of the models of concrete action of Crozier and Friedberg (1977) , the analysis of the action / situation the behavior of actors involved in winning projects. The methodology used in the design of this research is that connected to Ground Theory of Strauss (1967) which emphasizes that the construction of knowledge about certain objects should be thought of as minimal articulation of the basic concepts that would guide the coming and going between the observation - is ethnographic or in-depth interview - and confirmation and reconstruction in a more complex theory to be applied. The most immediate conclusion to studies runs through mid-range theories that allow a contact with the object of study whose proximity allows a process of discovery of the relevance of the central observation, as well as another pillar of theoretical investigations of the actors involved in international cooperation projects.